Transthoracic ultrasound guided fine needle aspiration cytology of peripheral lung lesions: an experience of a pulmonologist - Sultan, Sheikh Tariq; Dar, Khurshid Ahmad; Ansari, Mohd Haris Gulraize; Mehfooz, Nazia; Shah, Naveed Nazir; Farooq, Syed Suraiya; Datta, Bikram Singh; Malik, Abdul Hamid; Sheikh, Bilal Ahmad (International Journal of Research in Medical Sciences, 2019)
Background: Ultrasound (USG) guided fine needle aspiration cytology (FNAC) is a simple and cost-effective method for the diagnosis of various peripheral lung lesions. Being radiation free and easily available in most of centres, it has become an important diagnostic modality for early diagnosis of peripheral lung lesions. Besides procedure is simple and complications if occur, can be managed by a pulmonologist effectively. This study was aimed to evaluate the role of Transthoracic ultrasound guided FNAC in diagnosis of peripheral lung lesion. Methods: This prospective observational study was conducted at Government Chest Diseases Hospital Srinagar over a period of one year from January 2018-December 2018. 61 patients who fulfilled inclusion criteria were included in this study. After properly explaining the procedure and taking informed consent, USG guided FNAC was done in patients with peripheral lung lesions under local anaesthesia. Radiological and cytological data of enrolled patients was collected prospectively and analysed. Result: About 61 patients were included in this study comprising of 39 males and 22 females in age range of 17- 90 years. Malignancy was the most common cytological diagnosis (78.57%). while as benign diagnosis was reached in 21.43%. In 8.19% of patients, FNAC was inconclusive. Among the malignant group, adenocarcinoma (47.72%) was most common cytological diagnosis. The overall diagnostic yield of USG guided FNAC in this study was 91.8%. Conclusion: USG guided FNAC of peripheral lung lesions is a simple procedure with high accuracy and less complication rate which can be performed by a pulmonologist for diagnosis.